Community pharmacists’ use, perception and knowledge on dietary supplements: a cross sectional study - Bukic, Josipa (Pharm Pract (Granada), 2021)
BACKGROUND: Pharmacists are commonly tasked with recommending the appropriate dietary supplement and advising the patients of their correct and safe use. Previous research, conducted on pharmacy students, showed that they did not always use the evidence based sources of information, with personal use identified as a significant predictor influencing the decision to recommend a supplement. OBJECTIVES: To compare use, perceptions and knowledge of dietary supplements of pharmacists with different years of work experience and to explore factors that could influence their recommendation of supplements. METHODS: A questionnaire based cross-sectional study was conducted on Croatian community pharmacists in September 2017. The questionnaire explored pharmacists’ demographic characteristics, use, perceptions and knowledge of dietary supplements. Pharmacists (N=102) were divided in two groups based on their work experience: P0 (<10 years) and P1 (≥10 years). RESULTS: All included pharmacists had high knowledge scores without differences between groups (P0=10, IQR 9-12 vs P1=11, IQR 9-12, expressed as median and interquartile range (IQR), p=0.275). Less experienced pharmacists perceived there was less research conducted on the dietary supplements compared to their more experienced counterparts (P0=1, IQR 1-2 vs P1=2, IQR 2-3, expressed as median and interquartile range, p<0.001). Groups differed in sources used when choosing the appropriate supplement with P0 using higher quality sources such as systematic reviews in comparison to P1 (32.1% vs 8.7%, p=0.004). Pharmacists’ decision to recommend a dietary supplement was influenced by their personal use (odds ratio 0.216, 95%CI 0.068:0.689, p=0.01) and work experience (odds ratio 0.154, 95%CI 0.045:0.530, p=0.003). CONCLUSIONS: Pharmacists did not use the high quality sources when recommending dietary supplements and their decision to recommend the supplement was not based on objective evaluation of evidence. Further education about the practice of evidence-based pharmacy is necessary, with special emphasis on senior pharmacists who might have missed that aspect during their formal education.